2013
DOI: 10.1016/j.nbd.2012.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficiency of the autism candidate gene Neurobeachin induces autism-like behaviors and affects cellular and molecular processes of synaptic plasticity in mice

Abstract: Neurobeachin (NBEA), a brain-enriched multidomain scaffolding protein involved in neurotransmitter release and synaptic functioning, has been identified as a candidate gene for autism spectrum disorder (ASD) in four unrelated patients haploinsufficient for NBEA. The aim of this study was to map the behavioral phenotype of Nbea(+/-) mice in order to understand its contribution to the pathogenesis of ASD. ASD-like behavioral variables of Nbea(+/-) mice were related to basal neuronal activity in different brain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
62
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 62 publications
10
62
1
Order By: Relevance
“…Its role in binding protein kinase A has been confirmed in platelet studies of haploinsufficient mice showing platelet dense granules, a phenomenon also seen in haploinsufficient autistic patients (Nuytens et al, 2013). Additionally, it has neuron specific expression, is necessary for dendritic morphology and synaptogenesis (Miller et al, 2015) and is associated with trans- golgi trafficking of intracellular, tubulovesicular endomembranes (Wang et al, 2000).…”
Section: : Reviewmentioning
confidence: 73%
“…Its role in binding protein kinase A has been confirmed in platelet studies of haploinsufficient mice showing platelet dense granules, a phenomenon also seen in haploinsufficient autistic patients (Nuytens et al, 2013). Additionally, it has neuron specific expression, is necessary for dendritic morphology and synaptogenesis (Miller et al, 2015) and is associated with trans- golgi trafficking of intracellular, tubulovesicular endomembranes (Wang et al, 2000).…”
Section: : Reviewmentioning
confidence: 73%
“…Heterozygous mice for Dyt1, underlying DYT1 dystonia, display enhanced hippocampal LTP and motor deficits (Yokoi et al, 2015). Mice heterozygous for Neurobeachin, previously identified as an autism gene candidate, have enhanced CA1 LTP, altered self-grooming, social behaviors, contextual fear, and spatial learning and memory (Nuytens et al, 2013). Additionally, an adult rat model of depression showed a similar pattern of changes in LTP as seen in the KA-ELS rat after seizure, with no change in LTP 7 days, enhanced LTP 14 days, and impaired LTP 21 days following exposure to chronic unpredictable mild stress (Qiao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Nair et al showed that Nbea -/- neurons have lower level of glutamate- and GABA receptors on their surface, and that these receptors accumulate at the post-Golgi site where Nbea would normally be located (Nair et al, 2013). In addition, NBEA has been linked to autism and autism symptoms (Castermans et al, 2003; Nuytens et al, 2013; Smith et al, 2002). …”
Section: Discussionmentioning
confidence: 99%